Lack of association of increased antibody levels to mycobacterial hsp65 with rheumatoid arthritis: results from a study of disease discordant twin pairs. Issue 7 (July 1993) - Worthington, J; Rigby, A S; MacGregor, A J; Silman, A J; Carthy, D; Ollier, W E
Abstract : OBJECTIVES–To investigate the role of humoral immunity to mycobacterial hsp65 in the aetiology of rheumatoid arthritis. METHODS–Levels of IgG antibodies to recombinant mycobacterial hsp65 were measured by enzyme linked immunosorbent assay (ELISA) in serum samples of 152 twin pairs discordant for RA and in serum samples from 62 normal blood donors. RESULTS–No significant differences between antibody levels in the subjects with RA compared either with their unaffected twins or with a group of normal blood donors was observed. In the monozygotic twins there was a strong but negative association between levels of antibody to hsp65 and disease status. Zygosity, sex, and HLA status did not significantly affect levels of antibody to hsp65. CONCLUSION–Previous reports of an association between hsp65 and RA were not confirmed.